If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -2(x + 1) = 7x + -1 Reorder the terms: 1 + -2(1 + x) = 7x + -1 1 + (1 * -2 + x * -2) = 7x + -1 1 + (-2 + -2x) = 7x + -1 Combine like terms: 1 + -2 = -1 -1 + -2x = 7x + -1 Reorder the terms: -1 + -2x = -1 + 7x Add '1' to each side of the equation. -1 + 1 + -2x = -1 + 1 + 7x Combine like terms: -1 + 1 = 0 0 + -2x = -1 + 1 + 7x -2x = -1 + 1 + 7x Combine like terms: -1 + 1 = 0 -2x = 0 + 7x -2x = 7x Solving -2x = 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -2x + -7x = 7x + -7x Combine like terms: -2x + -7x = -9x -9x = 7x + -7x Combine like terms: 7x + -7x = 0 -9x = 0 Divide each side by '-9'. x = 0 Simplifying x = 0
| x=5y+2a | | h^2-144= | | 13-3a=8 | | 4z^4-12z^3+17Z^2-10z+2=0 | | 204=x^2+5x | | 2x^2=2+2x | | 2w^2+3w+1= | | 3x^2=5x-2 | | -.5x^2+x+24=0 | | -9x-7i= | | X^2-6=58 | | -3x^4+363=0 | | x^2-5x=4x | | 8h-10h=3h | | p^2+10p+25=0 | | h^2+7h-44=0 | | 2400=0.5(40)(15+x) | | .5x^2+x+24=0 | | 6x^2+7x+8=0 | | 400=0.5(3x) | | x+0.15x=30 | | 2x^2+5=-x | | 3(x+11)=68 | | 30-6(x-3)=9(x-5) | | 4(x-11)+6x=36 | | 3-3(x+6)=3 | | 5x+6(x-0)=11 | | 2y^3+5y^2+2y= | | 6x+6(x-4)=24 | | 20(x-3)+2x=56-2(x-4) | | 4-6(x+5)=4 | | 4d+2(d+3)=-3(d-2) |